Preparation method of sodium-ion battery positive electrode dry-method rapid homogenate

The sodium ion battery positive electrode slurry is prepared by dry process and modified carbon nanotubes are used as conductive agents, which solves the problems of low energy density and service life of sodium ion batteries, and achieves high-performance and low-energy-consuming battery production.

CN119517942APending Publication Date: 2025-02-25ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411730566.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The energy density and service life of existing sodium ion batteries are lower than that of lithium ion batteries, and the wet mixing process has problems such as high energy consumption, large environmental pollution, and long production cycle.

Method used

The sodium ion battery positive electrode slurry is prepared by dry process, and the kneaded slurry is prepared by powder mixing and stirring, high-speed dispersion and negative pressure defoaming treatment are obtained to obtain high-performance positive electrode slurry. Using modified carbon nanotubes as conductive agents, the intercalation and diffusion ability of sodium ions is improved by introducing phosphonic acid groups and other reactive groups.

Benefits of technology

It realizes the high energy density of sodium ion batteries, improves the stability and performance of the batteries, reduces the energy consumption and environmental pollution of production, and shortens the production cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517942A_ABST
    Figure CN119517942A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode dry method rapid homogenization preparation method, and belongs to the technical field of ion battery pulping processes, and the method comprises the following steps: S1-1, weighing a positive electrode main material, a conductive agent, an adhesive, oxalic acid and PVP, and carrying out powder mixing; s1-2, a solvent is added into the mixed powder, and kneading slurry is prepared through stirring; s1-3, adding a solvent into the kneaded slurry, and continuously stirring to prepare high-speed dispersed slurry; and S1-4, carrying out defoaming treatment on the obtained slurry dispersed at a high speed under a negative pressure condition to obtain the positive electrode slurry. The preparation method of the sodium ion battery is simple in process, low in cost, short in production period and capable of improving the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion battery pulping technology, and specifically relates to a method for preparing a sodium ion battery positive electrode dry rapid homogenization. Background Art

[0002] As the core component of new energy vehicles, power batteries are one of the keys to the development of new energy vehicles. With the rise in lithium-ion battery prices and limited resource reserves, sodium-ion batteries, which have a wide distribution of resources, have gradually come into people's view. Sodium-ion batteries are gaining more and more attention in the new energy vehicle industry because of their low cost and abundant sodium resource reserves.

[0003] In the field of battery manufacturing, the wet mixing process and its related improved technologies have been widely used in industrial production, and have mature processes and equipment. The process involves mixing active materials, conductive agents, binders, etc. into slurry in a liquid medium, then coating it on the current collector, and then drying, rolling, etc. to make electrodes.

[0004] The wet mixing process can achieve uniform mixing of various materials and ensure the stable performance of electrode materials. At the same time, the performance and production efficiency of electrodes can be further improved by optimizing process parameters and equipment configuration. However, the wet mixing process also has some limitations, such as high energy consumption, large environmental pollution, and long production cycle. These problems limit the application of the wet mixing process in sustainable development and cost control.

[0005] In addition, the energy density and service life of sodium-ion batteries are lower than those of lithium-ion batteries, which has a certain impact on the application scope of sodium-ion batteries. Therefore, it is necessary to seek a sodium-ion battery preparation method with simple process, low cost, short production cycle and improved battery performance. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a sodium ion battery positive electrode dry rapid homogenization, which adopts a dry process and has the advantages of low energy consumption, low environmental pollution, short production cycle, etc., and makes the sodium ion battery have a high energy density, improves the stability and battery performance of the obtained battery.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a sodium ion battery positive electrode dry rapid homogenization comprises the following steps: S1-1. Weigh the positive electrode material, conductive agent, binder, oxalic acid and PVP and mix the powders; S1-2. A solvent is added to the mixed powder, and a kneading slurry is prepared by stirring; S1-3. A solvent was added to the obtained kneaded slurry, and stirring was continued to prepare a high-speed dispersed slurry; S1-4. Degassing the obtained high-speed dispersed slurry under negative pressure to obtain positive electrode slurry.

[0008] Preferably, the positive electrode main material can be layered oxides, Prussian blue and its analogs, and polyanionic compounds.

[0009] Preferably, the adhesive includes at least one of PTFE, PVDF and PVA.

[0010] Preferably, the conductive agent includes at least one of a carbon material, a metal oxide and a conductive polymer.

[0011] Furthermore, the conductive agent includes at least one of Super P, Ketjen black, acetylene black, graphene, carbon nanotubes, and modified carbon nanotubes.

[0012] The use of carbon nanotubes or modified carbon nanotubes as conductive agents can significantly improve the performance of the resulting sodium ion battery. The use of carbon nanotubes or modified carbon nanotubes helps to form a good conductive network in the resulting positive electrode slurry, reduce internal resistance and make it less prone to polarization, thereby improving the performance of the resulting battery.

[0013] Furthermore, the modified carbon nanotubes have phosphonic acid groups.

[0014] Phosphonic acid groups are introduced on the surface of carbon nanotubes, so that the microstructure of the modified carbon nanotubes is changed, which is conducive to the embedding and de-embedding of sodium ions and can promote the diffusion of sodium ions in the electrolyte. In addition, the presence of phosphonic acid groups also helps to increase the activity of other groups on the surface of carbon nanotubes, further promoting the embedding and de-embedding of sodium ions, thereby helping to improve the performance of the resulting battery.

[0015] Furthermore, the modified carbon nanotubes have nitrilotrimethylenephosphonic acid and / or aminomethylphosphonic acid groups. Thus, not only phosphonic acid groups but also active groups such as amino groups and hydroxyl groups are introduced on the surface of the carbon nanotubes, thereby providing more embedding sites for sodium ions during the charge and discharge process, which helps to make up for the slow diffusion of sodium ions due to their larger ion radius.

[0016] Preferably, the mass ratio of the positive electrode main material, the conductive agent, the adhesive, the oxalic acid and the PVP is 60-95:2-4:1-3:0.1-0.5:0.1-0.5.

[0017] Preferably, in step S1-2, the solvent is NMP; the mass ratio of the positive electrode main material in S1-1 to the NMP in S1-2 is 2-5:1.

[0018] Preferably, in step S1-3, the solvent is NMP; the mass ratio of the total amount of NMP in S1-2 to the total amount of NMP in S1-3 is 1-3:3-6.

[0019] Preferably, in step S1-3, the solvent is added multiple times.

[0020] According to one aspect of the present invention, there is provided a method for preparing modified carbon nanotubes, comprising the following steps: S2-1. Add nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid to carbon nanotubes, stir and seal, react at 55-80°C for 12-36h, then heat to 100-150°C for 2-6h.

[0021] S2-2. After the reaction system in S2-1 is cooled to 20-30°C, a Tris buffer is added thereto and ultrasonicated for 15-40 minutes, and then 3-hydroxypyrrolidine is added thereto and ultrasonicated for 15-40 minutes. Then, after stirring for 6-10 hours, the mixture is filtered and washed, and then vacuum dried to obtain modified carbon nanotubes.

[0022] Preferably, in step S2-1, the mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid is 1-3:0.5-1.5:0.5-1.5.

[0023] Preferably, in step S2-1, the stirring speed is 120-200 r / min, and the stirring time is 10-60 min.

[0024] Preferably, the mass volume ratio of the amount of carbon nanotubes in S2-1 to the amount of 3-hydroxypyrrolidine in S2-2 is 1 g: 3-8 mL.

[0025] Preferably, in step S2-2, the pH of the Tris buffer is 8-9; the vacuum drying temperature is 40-70°C, and the drying time is 2-6h.

[0026] In the process of modifying carbon nanotubes, the use of modifiers nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid introduces phosphonic acid groups on the surface of carbon nanotubes, and grafts 3-hydroxypyrrolidine groups. The phosphonic acid groups and the heterocyclic structure in the 3-hydroxypyrrolidine groups change the spatial structure of the modified carbon nanotubes, which is helpful for the embedding and de-embedding of sodium ions and can promote the diffusion of sodium ions in the electrolyte.

[0027] Furthermore, in the method for preparing modified carbon nanotubes, in step S2-1, 4-aminobutane-1-phosphoric acid is added while adding nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid.

[0028] Preferably, the mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid, aminomethylphosphonic acid and 4-aminobutane-1-phosphoric acid is 1-3:0.5-1.5:0.5-1.5:0.5-1.5.

[0029] According to one aspect of the present invention, a sodium ion battery positive electrode sheet is provided, comprising: a base layer, and a functional layer attached to the base layer, wherein the functional layer comprises a positive electrode slurry obtained by any one of the above preparation methods.

[0030] According to one aspect of the present invention, a sodium ion battery is provided, comprising the above-mentioned sodium ion battery positive electrode sheet.

[0031] The present invention also discloses the application of the sodium ion battery in vehicles, and the vehicles include electric vehicles, electric forklifts, electric transport trucks, etc.

[0032] Compared with the prior art, the present invention has the following beneficial effects: The dry process is used to prepare the positive electrode slurry of the sodium ion battery. Compared with the wet mixing process, the amount of liquid medium used is small, so it has the advantages of low energy consumption, less environmental pollution, and short production cycle; and the dry process can also achieve a more accurate material ratio and a more uniform mixing effect, thereby improving the performance and stability of the electrode. Compared with Super P, the use of carbon nanotubes or modified carbon nanotubes as a conductive agent can significantly improve the performance of the resulting sodium ion battery, improve the battery's first coulomb efficiency, positive electrode energy density and capacity retention rate. The use of carbon nanotubes or modified carbon nanotubes helps to form a good conductive network in the resulting positive electrode slurry, reduce internal resistance and is not easy to polarize, thereby improving the performance of the resulting battery. In addition, the use of modified carbon nanotubes as a conductive agent further improves the performance of the resulting sodium ion battery. In the process of modifying carbon nanotubes, the use of modifiers nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid introduces phosphonic acid groups on the surface of carbon nanotubes, and grafts 3-hydroxypyrrolidine groups, phosphonic acid groups and heterocyclic structures in 3-hydroxypyrrolidine groups, so that the spatial structure of the modified carbon nanotubes changes, which is conducive to the embedding and de-embedding of sodium ions and can promote the diffusion of sodium ions in the electrolyte. The surface of the modified carbon nanotubes introduced active groups such as amino groups, hydroxyl groups, and organic acids, so that more embedding sites can be provided for sodium ions during the charge and discharge process, making up for the lack of slow diffusion of sodium ions due to their large ionic radius. In addition, the introduction of phosphonic acid groups in the modified carbon nanotubes makes it easier for the modified carbon nanotubes to overlap and entangle with the active materials in the positive electrode material, which also helps to enhance the toughness of the electrode; in addition, the introduction of heteroatoms in the process of carbon nanotube modification also helps to improve the conductivity of the obtained positive electrode slurry and improve the electrochemical performance. In the process of modifying carbon nanotubes, an appropriate amount of 4-aminobutane-1-phosphoric acid is added to the modifiers nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid, and short-chain alkane groups are introduced on the surface of the modified carbon nanotubes. Under the influence of phosphonic acid / phosphoric acid groups and amino groups, the short-chain properties grafted on the surface of the carbon nanotubes are more active, so that sodium ions and the like are more easily adsorbed and desorbed from the surface of the carbon nanotubes during the charge and discharge process of the sodium ion battery, thereby exhibiting better electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is an infrared spectrum of the modified carbon nanotubes obtained according to Example 2 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] Example 1 Preparation of cathode materials S1-1. Weigh the positive electrode material Na3V2(PO4)3, the conductive agent Super P, the adhesive PVDF, oxalic acid and PVP; the mass ratio of the positive electrode material, the conductive agent, the adhesive, the oxalic acid and the PVP is 70:2.5:1.5:0.2:0.1. Put the above materials into a stirring tank, revolve at -5RPM, rotate at 0RPM, stir for 30min, then revolve at 30RPM, rotate at 500RPM, stir for 30min, and mix the powders.

[0035] S1-2. NMP was added to the mixed powder obtained in S1-1, and preliminary kneading was performed with revolution 10RPM, rotation 0RPM, and stirring time 10min, and then kneading was performed with revolution 30RPM, rotation 0RPM, and stirring time 90min to prepare a kneaded slurry.

[0036] Among them, the mass ratio of the positive electrode main material in S1-1 to NMP in S1-2 is 3:1.

[0037] S1-3. Add NMP twice to the kneaded slurry obtained in S1-2. After each addition of NMP, perform high-speed dispersion at 20RPM and 2000RPM rotation. Stir for 60 minutes to prepare a high-speed dispersed slurry with a viscosity requirement of 2000-5000cp and a fineness requirement of ≤30μm.

[0038] Among them, the mass ratio of the total amount of NMP in S1-2 to that in S1-3 is 2:3; the mass ratio of the two amounts of NMP used in S1-3 is 2:1.

[0039] S1-4. The high-speed dispersed slurry obtained in S1-3 was subjected to vacuum degassing treatment at -0.07MPa to -0.02MPa by revolving at -5RPM (reverse) and rotating at 0RPM for 60 minutes to remove bubbles in the slurry.

[0040] Preparation of positive electrode The positive electrode slurry obtained above was extrusion coated on the aluminum foil, and the coating amount on one side was 0.015 g / cm 2 The positive electrode sheet is obtained through drying, compacting, rolling and cutting.

[0041] Preparation of sodium ion batteries A hard carbon negative electrode sheet and a PP separator are used in combination with the positive electrode sheet obtained above, and a dry cell is assembled in a stacking manner, and then encapsulated with an aluminum plastic film, and an electrolyte is injected, and then the formation is waited for, and the formation upper limit voltage is controlled to 4.0V-4.5V. The obtained cell is further assembled into a battery.

[0042] Example 2 The difference between this embodiment and embodiment 1 is that during the preparation of the positive electrode material, the conductive agent is replaced with modified carbon nanotubes of equal mass. Other conditions and steps are the same.

[0043] Wherein, the preparation method of modified carbon nanotubes is as follows: S2-1. Add nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid to carbon nanotubes, stir at 150 r / min for 30 min, seal, react at 70°C for 24 h, and then heat to 120°C for 4 h.

[0044] The mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid is 2:1:1.

[0045] S2-2. After the reaction system in S2-1 is cooled to 25°C, Tris buffer (pH=8.5) is added thereto and ultrasonicated for 30 minutes, and then 3-hydroxypyrrolidine is added thereto and ultrasonicated for 30 minutes. Then, after stirring at 150 r / min for 8 hours, the mixture is filtered, washed with deionized water, and vacuum dried at 55°C for 4 hours to obtain modified carbon nanotubes.

[0046] Among them, the mass volume ratio of the amount of carbon nanotubes in S2-1 to the amount of Tris buffer in S2-2 is 1g:5mL; the mass volume ratio of the amount of carbon nanotubes in S2-1 to the amount of 3-hydroxypyrrolidine in S2-2 is 1g:5mL.

[0047] The obtained modified carbon nanotubes and carbon nanotube raw materials were characterized by Fourier transform infrared spectroscopy. The samples were prepared by potassium bromide tablet method with a scanning wavelength range of 500 cm -1 ~4000cm -1 ; Scan line number is 32; Resolution is 4cm -1 ; The obtained infrared spectrum is shown in Figure 1 As can be seen from the figure, the modified carbon nanotubes have a wavelength of 34300 cm -1 There are strong absorption peaks near 1630cm -1 The vibrating band is generated by the stretching vibration of the carbon-carbon double bond on the carbon nanotube, 1120 cm -1 The characteristic peak nearby is the absorption peak of P=O, which shows that the phosphonic acid groups are successfully grafted onto the modified carbon nanotubes.

[0048] Example 3 Compared with Example 1, this embodiment is different in that: in the preparation process of the positive electrode material, the conductive agent is replaced by modified carbon nanotubes, and the modified carbon nanotubes account for 3 parts by weight. The preparation method of the modified carbon nanotubes is the same as that of Example 2. Other conditions and steps are the same.

[0049] Example 4 Compared with Example 1, this embodiment is different in that: in the preparation process of the positive electrode material, the conductive agent is replaced by modified carbon nanotubes, and the modified carbon nanotubes account for 3.5 parts by weight. The preparation method of the modified carbon nanotubes is the same as that of Example 2. Other conditions and steps are the same.

[0050] Example 5 Compared with Example 2, the present embodiment is different in that: in the preparation method of modified carbon nanotubes, in step S2-1, 4-aminobutane-1-phosphoric acid is added while adding nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid, and the mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid, aminomethylphosphonic acid and 4-aminobutane-1-phosphoric acid is 2:1:1:0.5.

[0051] The other conditions and steps were the same.

[0052] Example 6 Compared with Example 2, this embodiment is different in that: in the preparation method of modified carbon nanotubes, in step S2-1, 4-aminobutane-1-phosphoric acid is added while adding nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid, and the mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid, aminomethylphosphonic acid and 4-aminobutane-1-phosphoric acid is 2:1:1:1.

[0053] The other conditions and steps were the same.

[0054] Comparative Example 1 The difference between this comparative example and Example 1 is that during the preparation of the positive electrode material, the conductive agent is replaced with carbon nanotubes of equal mass. Other conditions and steps are the same.

[0055] Comparative Example 2 The difference between this comparative example and Example 2 is that in the method for preparing modified carbon nanotubes, in step S2-1, aminomethylphosphonic acid is replaced with an equal mass of nitrilotrimethylenephosphonic acid. Other conditions and steps are the same.

[0056] Comparative Example 3 The difference between this comparative example and Example 2 is that in the method for preparing modified carbon nanotubes, in step S2-1, nitrilotrimethylenephosphonic acid is replaced with aminomethylphosphonic acid of equal mass. Other conditions and steps are the same.

[0057] Test example Electrochemical performance test Battery tests were performed on the batteries prepared in Examples 1-6 and Comparative Examples 1-3.

[0058] The constant current charge-discharge test and cycle life test of the battery were carried out by Xinwei CT4000, and the voltage and electrochemical impedance test of the cyclic voltammetry test were carried out by Chenhua CHI760D electrochemical workstation. The test voltage window was 2.0-4.5 V, and the current density was 1 C=100 mA g -1 .

[0059] For the batteries obtained in Examples 1-6 and Comparative Examples 1-3, the first charge and discharge capacity was tested at a 50C rate and the first coulombic efficiency was calculated. The results of the first coulombic efficiency test are shown in Table 1.

[0060] Table 1 The first coulombic efficiency test results of each embodiment and comparative example

[0061] Referring to the data in Table 1, the first coulombic efficiency of the batteries obtained in Examples 2-6 and Comparative Examples 1-3 increased by 10.5%, 12.1%, 13.2%, 16.1%, 17.1%, 5.1%, 8.8% and 7.7% respectively compared with Example 1. It can be seen that the use of carbon nanotubes or modified carbon nanotubes as conductive agents can significantly improve the first coulombic efficiency of sodium ion batteries compared with Super P.

[0062] Compared with Example 1, the first coulombic efficiency of the batteries obtained in Examples 2-4 is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the first efficiency of the obtained sodium ion battery.

[0063] Compared with Comparative Example 1, the first coulombic efficiency of the batteries obtained in Examples 2-4 and Comparative Examples 2-3 increased by 5.2%, 6.6%, 7.7%, 3.5% and 2.5%, respectively. It can be seen that compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more obvious effect on the first coulombic efficiency of the obtained sodium ion battery. In addition, during the modification of the carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid are used as modifiers. Compared with the use of nitrilotrimethylenephosphonic acid or aminomethylphosphonic acid alone as a modifier, the modified carbon nanotubes have a more significant effect on the first coulombic efficiency of the sodium ion battery.

[0064] Compared with Example 2, the first coulombic efficiency of the batteries obtained in Examples 5-6 increased by 5.0% and 5.9%, respectively. It can be seen that in the process of carbon nanotube modification, adding an appropriate amount of 4-aminobutane-1-phosphoric acid to the modifiers nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid, the modified carbon nanotubes have a more significant effect on the first coulombic efficiency of the sodium ion battery; and within a certain range, the first coulombic efficiency of the sodium ion battery is positively correlated with the amount of 4-aminobutane-1-phosphoric acid used.

[0065] For the batteries prepared in Examples 1-6 and Comparative Examples 1-3, the capacity of the batteries was obtained by charging to 4.0V at 0.5C constant current and constant voltage, and discharging to 1.5V at 0.5C. The weight of the battery cell was measured with a balance, and the energy density of the battery cell was calculated. The positive electrode energy density test results are shown in Table 2.

[0066] Table 2 Test results of positive electrode energy density of various embodiments and comparative examples

[0067] Referring to the data in Table 2, the positive electrode energy density of the batteries obtained in Examples 2-6 and Comparative Examples 1-3 increased by 11.6%, 14.7%, 17.0%, 19.4%, 22.5%, 3.1%, 9.3% and 7.8% respectively compared with Example 1. It can be seen that the use of carbon nanotubes or modified carbon nanotubes as conductive agents can significantly improve the positive electrode energy density of sodium ion batteries compared with Super P.

[0068] Compared with Example 1, the positive electrode energy density of the batteries obtained in Examples 2-4 is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the positive electrode energy density of the obtained sodium ion battery.

[0069] Compared with Comparative Example 1, the positive electrode energy density of the batteries obtained in Examples 2-4 and Comparative Example 2-3 increased by 8.2%, 11.3%, 13.5%, 6.0% and 4.5%, respectively. It can be seen that compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more obvious effect on the positive electrode energy density of the obtained sodium ion battery. In addition, during the modification of the carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid are used as modifiers. Compared with the use of nitrilotrimethylenephosphonic acid or aminomethylphosphonic acid alone as a modifier, the modified carbon nanotubes have a more significant effect on the positive electrode energy density of the sodium ion battery.

[0070] Compared with Example 2, the positive electrode energy density of the battery obtained in Examples 5-6 increased by 6.9% and 9.7%, respectively. It can be seen that in the process of carbon nanotube modification, adding an appropriate amount of 4-aminobutane-1-phosphoric acid to the modifiers nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid, the modified carbon nanotubes have a more significant effect on the positive electrode energy density of the sodium ion battery; and within a certain range, the positive electrode energy density of the obtained sodium ion battery is positively correlated with the amount of 4-aminobutane-1-phosphoric acid used.

[0071] For the batteries prepared in Examples 1-6 and Comparative Examples 1-3, the cycle performance was tested for 400 cycles using a 1C rate charge / discharge test. The capacity retention test results are shown in Table 3.

[0072] Table 3 Capacity retention test results after 400 cycles of various embodiments and comparative examples

[0073] Referring to the data in Table 3, the capacity retention rates of the batteries obtained in Examples 2-6 and Comparative Examples 1-3 after 400 cycles were increased by 7.7%, 9.5%, 11.1%, 13.0%, 13.4%, 2.5%, 6.4% and 5.5%, respectively, compared with Example 1. It can be seen that the use of carbon nanotubes or modified carbon nanotubes as conductive agents can significantly improve the capacity retention rate of sodium ion batteries compared with Super P.

[0074] Compared with Example 1, the capacity retention rate of the batteries obtained in Examples 2-4 after 400 cycles is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the capacity retention rate of the obtained sodium ion battery.

[0075] Compared with Comparative Example 1, the capacity retention rates of the batteries obtained in Examples 2-4 and Comparative Example 2-3 were increased by 5.0%, 6.8%, 8.3%, 3.8% and 2.9%, respectively. It can be seen that compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more significant effect on the capacity retention rate of the obtained sodium ion battery. In addition, during the modification of the carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid are used as modifiers. Compared with the use of nitrilotrimethylenephosphonic acid or aminomethylphosphonic acid alone as a modifier, the modified carbon nanotubes have a more significant effect on the capacity retention rate of the sodium ion battery.

[0076] Compared with Example 2, the positive electrode energy density of the battery obtained in Examples 5-6 increased by 5.0% and 5.3%, respectively. It can be seen that in the process of carbon nanotube modification, adding an appropriate amount of 4-aminobutane-1-phosphoric acid to the modifiers nitrilo trimethylenephosphonic acid and aminomethylphosphonic acid, the modified carbon nanotubes have a more significant effect on the capacity retention rate of the sodium ion battery; and within a certain range, the capacity retention rate of the obtained sodium ion battery is positively correlated with the amount of 4-aminobutane-1-phosphoric acid. This may be because, in the process of modifying the carbon nanotubes, the use of the modifiers nitrilo trimethylenephosphonic acid and aminomethylphosphonic acid introduces phosphonic acid groups on the surface of the carbon nanotubes, making it easier for the modified carbon nanotubes to overlap and entangle with the active materials in the positive electrode material, thereby enhancing the toughness of the electrode. However, the use of 4-aminobutane-1-phosphoric acid introduces short-chain alkane groups on the surface of the modified carbon nanotubes. Under the influence of phosphonic acid / phosphoric acid groups and amino groups, the short-chain properties grafted on the surface of the carbon nanotubes are more active, so that sodium ions are more easily adsorbed and desorbed from the surface of the carbon nanotubes during the charge and discharge process of the sodium ion battery, thereby showing better cycle performance.

[0077] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0078] The above-described embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above-described embodiments are only specific embodiments of the present invention and are not intended to limit the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a sodium ion battery positive electrode by dry rapid homogenization, comprising the following steps: S1-1 weighing the cathode material, conductive agent, binder and oxalic acid and PVP, powder mixing; the conductive agent includes Super P, Ketjen black, acetylene black, graphene, carbon nanotubes, modified carbon nanotubes in at least one; modified carbon nanotubes having a phosphonic acid group; S1-2. A solvent is added to the mixed powder, and a kneading slurry is prepared by stirring; S1-3. A solvent was added to the obtained kneaded slurry, and stirring was continued to prepare a high-speed dispersed slurry; S1-4. The obtained high-speed dispersed slurry is degassed under negative pressure to obtain a positive electrode slurry.

2. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 1, characterized in that: The mass ratio of the positive electrode main material, the conductive agent, the adhesive, the oxalic acid and the PVP is 60-95:2-4:1-3:0.1-0.5:0.1-0.

5.

3. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 1, characterized in that: The modified carbon nanotubes have nitrilotrimethylenephosphonic acid and / or aminomethylphosphonic acid groups.

4. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 3, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: S2-1. Add nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid to the carbon nanotubes, stir and seal, react at 55-80°C for 12-36h, then heat to 100-150°C for 2-6h; S2-2. After the reaction system in S2-1 is cooled to 20-30°C, Tris buffer is added thereto and ultrasonicated for 15-40 minutes, and then 3-hydroxypyrrolidine is added thereto and ultrasonicated for 15-40 minutes; then stirred for 6-10 hours, filtered and washed, and vacuum dried to obtain modified carbon nanotubes.

5. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 4, characterized in that: In step S2-1, the mass ratio of carbon nanotubes, nitrilotrimethylenephosphonic acid and aminomethylphosphonic acid is 1-3:0.5-1.5:0.5-1.

5.

6. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 4, characterized in that: The mass volume ratio of the amount of carbon nanotubes in S2-1 to the amount of 3-hydroxypyrrolidine in S2-2 is 1 g:3-8 mL.

7. The method for preparing a sodium ion battery positive electrode dry rapid homogenization according to claim 4, characterized in that: In step S2-2, the pH of the Tris buffer is 8-9; the vacuum drying temperature is 40-70°C, and the drying time is 2-6 hours.

8. A sodium ion battery positive electrode sheet, characterized in that: include: A substrate layer, and a functional layer attached to the substrate layer, wherein the functional layer comprises a positive electrode slurry obtained by any one of the preparation methods of claims 1-7.

9. A sodium ion battery, comprising the sodium ion battery positive electrode sheet according to claim 8.

10. A vehicle comprising the sodium ion battery according to claim 9.